One-pot synthesis of N-doped graphene for metal-free advanced oxidation processes - Wang, C.; Kang, J.; Sun, Hongqi; Ang, Ming; Tadé, Moses; Wang, Shaobin (Pergamon, 2016)
Recently, graphene and its derivatives as novel metal-free materials have attracted considerable attention in environmental remediation technologies. One of the barriers to practical applications is the mass production of high quality graphene-based catalysts. In this study, high-quality nitrogen-doped graphene (NG) nanomaterials were synthesized by controlled pyrolysis of a mixture of glucose, ferric chloride and urea. Glucose serves as a carbon precursor, urea as a nitrogen precursor, and hexahydrate ferric chloride as both a template and a catalyst. It was found that a low oxygen level of 2-4 at% and a nitrogen doping level of 0.5-1.8 at% were achieved at a moderate temperature. The obtained nitrogen-doped graphene was employed as a metal-free catalyst for efficient phenol degradation by peroxymonosulfate (PMS) activation. Kinetic studies showed that the phenol degradation facilitated by NG catalysis followed first-order reaction kinetics. Electron paramagnetic resonance (EPR) was performed to detect radical generation in order to reveal the mechanism of PMS activation processes and phenol degradation pathways on nanocarbons. It was found that both •OH and SO4 •- were produced in the catalytic oxidation processes and played significant roles in phenol oxidation.